IMPLEMENTING GAMIFICATION WITH THE PEACEGEN APPLICATION TO ENHANCE STUDENT ENGAGEMENT AND MOTIVATION IN CLASS VII A AT SMPN 1 LABUAPI, WEST LOMBOK: AN ACTION RESEARCH STUDY - Prasetyo, Anggoro Eko; Mubin, Ilmiawan; Anshori, Ahmad; Rukmini, Rukmini (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2023)
Abstract